PERADABAN DAN PEMIKIRAN ISLAM PADA MASA NABI MUHAMMAD SAW - Lesnida Lesnida; Haidar Putra Daulay; Zaini Dahlan (Tsaqofah dan Tarikh: Jurnal Kebudayaan dan Sejarah Islam, 2021)
Abstract: This study aims to determine 1) how Islamic civilization was at the time of the Prophet Muhammad. 2) how Islamic thought at the time of the Prophet Muhammad. To find out these two problems, the authors analyzed Islamic civilization and thought at the time of the Prophet Muhammad. in terms of Islamic history during the leadership of the Prophet. This study uses historical research methods. The research method used is to use the historical research method, namely a system of the correct ways to reach historical truth. The results of the research show that there is a figure of the Messenger of Allah SWT. namely, a servant whose presence is eagerly awaited to be able to save and free from the bondage of idolatry. In the midst of a society that is ignorant and perverted, Allah SWT. sent a prophet who gave the right guidance and light, he was the Prophet Muhammad. He was sent with a treatise or teachings from the creator. Give instructions to them about who really has the right to be worshiped and asked for help. Explaining to them the straight path again saves. The Koran and the Sunnah brought real changes to Arabs and nations who embraced Islam. The following article describes the civilization and thought of Islam at the time of the prophet Muhammad. Keywords: civilization, thought, Islam, the time of the Prophet Muhammad